Penerapan Metode Regresi Linear Berganda Dalam Sistem Prediksi Nilai Ujian Nasional Siswa SMP - Masruroh Masruroh; Kemal Farouq Mauladi (Jurnal Teknika, 2020)
The national examination result is no longer be used as a passing student determining factor, but it can be used as a reference for the schools to determine school’s policy in the future. So far the prediction of the results of the national examination has not been carried out systematically, therefore this system of national examination result prediction is expected to help the stakeholder in the prediction process. In this research, the method of linear regression will be implemented in the system of national examination result prediction web-based. The data used in the trial of linear regression method implementation in the system as much as 45 data. The result showed that the linear regression method can be implemented in the system of national examination result prediction with average MSE about 8,68 and average MAPE about 10.15%.